Improved Precoder Architecture for Duobinary Transceivers - Aguirre Olcoz, Javier; Sánchez-Azqueta, C.; Guerrero, E.; Gimeno, C.; Celma, S. (Jornada de Jóvenes Investigadores del I3A, 2017)
Duobinary modulation is an attractive baseband modulation scheme for high-speed serial data transmission. This work presents a duobinary transceiver with a new precoder architecture that overcomes the glitch vulnerability of the conventional ones. It has been fabricated in a 0.13-μm PD-SOI CMOS technology and achieves 10 Gbps consuming 37 mW.